Methanol electro-oxidation using Rurh@Pt/C - Guang Ying Wang (2018)
A core-shell structure RuRh@Pt/C nanoparticles was prepared by using a two-step reduction method under ultrasonic promotion. The catalytic performance was tested in methanol electrooxidation. X-ray diffraction (XRD), scanning electron microscope (SEM) combined with cyclic voltammetry (CV) were used to characterize the obtained catalyst. The results showed that there was no alloy formed between the core RuRh and the shell Pt. The electrocatalytic activity of RuRh@Pt/C varied with the Ru/Rh ratio in the bimetallic core, among which the catalyst with the Ru/Rh ratio 1:2 and the Pt-shell thickness of 1.5 (Ru1Rh2@Pt1.5/C) showed the highest catalytic activity for methanol. With this catalyst, the current density of the oxidation peak for methanol electro-oxidation reached 2.3 times as that of Pt1.5/C while the corresponding peak potential shifted 60 mV negatively in comparing to that of Pt1.5/C. In addition, the catalyst with the core-shell structure of RuRh@Pt/C possessed much higher CO-tolerance for methanol electro-oxidation, indicating its promising application in low temperature fuel cell. © (2014) Trans Tech Publications, Switzerland.